Strategies for Overcoming Socio-Economic Challenges Encountered by Different Professions During COVID-19 Pandemic - Malakar, Indra Mali; Lama, Ramesh Kumar; Sapkota, Bhaba Datta (Far Western Review, 2024)
The Nepalese economy has been severely impacted by the pandemic. This study analyzed the socio-economic challenges encountered by different professions during the COVID-19 pandemic and their strategies in the Kathmandu district. The study, using a pragmatic approach with both deductive and inductive reasoning, focused on Kirtipur Municipality, Kathmandu Metropolitan City, and Gokarneshwor Municipality. It included private school teachers, daily wage workers, small business owners, farmers, and transportation laborers. A cluster-stratified sampling design was used, with a sample size of 324 determined by Cochran’s formula. Data were collected through questionnaires, focus group discussions (FGDs), and key informant interviews (KIIs) and analyzed using a descriptive survey design. The study found that 85.8 percent of respondents were literate, with a mean age of 33.94 years. Reduced sales, unpaid wages, and inability to pay rent or loans were common, causing stress and health concerns. Financial struggles were highest in Gokarneshwor (80.6%), followed by Kirtipur (74.1%) and Kathmandu (62%). About 75.3 percent struggled with daily food due to lock downs, inflation, and limited necessities. While 87.3 percent had savings pre-pandemic, 50.5 percent found them useful, especially literate individuals and shop owners. The study result found that responsible consumption is a strategic way to sustain life. Equally, saving habits, storing food, engaging in small-scale farming, sanitation, adopting self-sustaining practices, vaccinations, and managing social capital are key strategies to strengthen economic resilience and cope with livelihood challenges.